Assessment of Voice Controlled Industrial Parameters Monitoring and Controlling System: An Update - Saurabh Sathawane; A. D. Belsare; Vaibhav Deshpande; Snehal Warade; Tanay Thakre (Theory and Applications of Engineering Research Vol. 7, 2024)
In this paper, we are proposing a system that allows humans to monitor and control Industry motor automatically. Its advantage is that if suddenly any system is not working properly in the industry and there is no worker available near the system then it will automatically perform certain actions accordingly. Through the Internet of Things, we may operate our appliances from any location in the globe. In the industrial sector, worker irresponsibility is frequently the cause of accidents, and there are certain hazardous places where workers are unable to perform their jobs. Voice-controlled Industrial parameters monitoring and controlling system are used in the risky areas of Industries usually in power plants where there are high noise level and pollution to avoid accidents. Here an induction motor speed, temperature, pressure, etc are monitored and controlled to avoid damage to the motor. These all the parameters are going to monitor and controlled automatically. In this paper, Google-Assistant and Adafruit IO server are used for monitoring and controlling. By using this system the workers can monitor and control Industrial appliances and problems occur in Industries where workers not able to go and work are overcome. By using this system, we can monitor Industrial appliances and its parameters on the Adafruit IO server and control it by using voice commands through Google Assistant.